Islamic Education as a Social Tool for Breaking the Cycle of Poverty - Adam Adam; Azhar Azhar; Muhammad Andi; Ahmad Audar; Ruslan Ruslan; Nasaruddin Nasaruddin (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the role of Islamic education as a social instrument in breaking the cycle of poverty in society and to identify the Islamic values that are internalized through Islamic education and contribute to the development of a work ethic, self-reliance, and social solidarity among the poor, as well as to analyze the most effective conceptual model for integrating Islamic educational values with socio-economic strategies to break the cycle of poverty sustainably. The approach used is qualitative library-based research, examining various academic and empirical literature. The research findings indicate that Islamic educational institutions play a role in strengthening social awareness and fostering robust spirituality as a bridge to breaking the cycle of poverty. Islamic values such as hard work, self-reliance, and sosial solidarity are internalized through Islamic education to cultivate religious and productive individuals. An effective conceptual model in Islamic education emphasizes value-based transformative education, socio-economic empowerment, and sustainable multisectoral collaboration; an Islamic spiritual-economic approach; a contextual and participatory multisectoral collaboration framework; and the integration of a values-based curriculum with practical social experiences.